Effect of Some Compounds on the α- Amylase Isoenzymes Activity purified from Abena -48 Wheat Flour Treated by Tribolium Confusum - Sameera Al-Katib (College of Education for Pure Sciences, 2005)
a- amylase was purified from Abena - 48 wheat flour treated by Tribolium confusum using heat treatment, ammonium sulfate precipitation (NH4)2SO4, dialysis and anion exchanger chromatography DEAE-cellulose. .Five isoenzymes were optained I, II, III, IV & V with elution volume of 30, 30, 40, 40, & 20 ml respectively, and with specific activity of 105120, 97333, 67384, 75703 & 85800 mu/mg protein respectively compared with the crude enzyme. Effects of some inhibitors and activators on the a- amylase isoenzymes activity were studied. Phenyl hydrazine showed an inhibitory effect between (66.7-77.8)%, EDTA snowed an inhibitory effect between (29.6-96.5)%, while the hydrochloric acid showed and inhibitory effect between (49.6-70.0)%. Heavy metal ions showed a different inhibitory effects on the a- amylase isoenzymes activity Cu+2 showed an inhibitory effect between (8.5-46.1)%, while Fe+2 showed an inhibitory effect between (4.8-57.6)%. No inhibitory effect was shown for iodoacetamide on the a- amylase ' isoenzymes activity, and insignificant inhibitory effect was shown with Triglycerate. Calcium and chloride ions showed activitory effects on the a- amylase isoenzymes activity I, II, III, IV & V. Ca+2 showed an activitory effect between (37.2-85.2)%, while CI showed an activitory effect between (31.0-91.1)%.